IMPROVING THE COMPETITIVENESS OF VOCATIONAL SCHOOL GRADUATES IN INDONESIA AS HUMAN CAPITAL THROUGH LOCAL WISDOM-BASED LEARNING - Ranu, Meylia Elizabeth; Hadi, Syamsul; Kurniawan, Riza Yonisa; Prakoso, Albrian Fiky (Universitas Labuhanbatu, 2025)
Purpose – The purpose of this study is to identify and analyze local wisdom values in each region in Indonesia that can be involved in education at Vocational High Schools, in order to increase the competitiveness of vocational high school graduates as human capital.Methodology – The research method employed in this study is a qualitative descriptive approach, focusing on productive subject teachers in vocational high schools of East Java Province. The collection of research data employed an interview method, utilizing an interview guide instrument, and was conducted through focus group discussions based on the spectrum of vocational expertise. FGD involved three productive subject teachers, the principal, and stakeholders, totaling N = 176. The data analysis in the study employed the interactive model of Miles and Huberman.Findings – Diploma ranks highest as the minimum education standard required by various job vacancies, at 52.8%, followed by Vocational High School at 30%. The requirement for a Bachelor's degree is 8.5%, then High School at 7.5%, and finally, the minimum requirement for postgraduate studies is 1.4%. The less-than-optimal absorption of Vocational High School graduates into the job market, based on existing vacancies, indicates that the industrial world is not yet fully convinced of the value of Vocational High School graduates for several fields of expertise.Contribution – This study contributes to identifying human capital development strategies, summarized based on local wisdom practices, by implementing key features such as developing global skills, described in basic skills, continuous learning and improvement, knowledge creation and sharing, systematic change, fostering a learning culture, encouraging experimentation, and appreciating students.